The wedding dress - Hauck, Rachel (Thomas Nelson, 2012)
"One dress. Four women. An amazing destiny. Charlotte Malone is getting married. Yet all is not settled in the heart of Birmingham's chic bridal boutique owner. Charlotte can dress any bride to perfection-except herself. When she discovers a vintage mint-condition wedding gown in a battered old trunk, Charlotte embarks on a passionate journey to discover the women who wore the gown before her. Emily in 1912. Mary in 1939. And Hillary in 1968. Each woman teaches Charlotte something about love in her own unique way. Woven within the threads of the beautiful hundred-year-old gown is the truth about Charlotte's heritage, the power of faith, and the beauty of finding true love"--